1999
DOI: 10.2527/1999.7782143x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trimethylamine oxide and betaine in swine diets on growth performance, carcass characteristics, nutrient digestibility, and sensory quality of pork.

Abstract: Two growth experiments and one digestibility experiment were conducted to study the effect of trimethylamine oxide (TMAO) and betaine in swine diets. In Exp. 1, 36 limit-fed pigs averaging 19.1 kg in initial weight were used to study the effect of adding TMAO at 10 g/kg of feed or betaine at an equivalent level of methyl groups (10.5 g/kg feed) to a high-fat (11.3% ether extract) basal diet. Dietary addition of TMAO increased ADG by 61 g/d, reduced number of days to market by 8.3 d (P<.02), and tended (P<.09) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 14 publications
6
35
2
1
Order By: Relevance
“…However, contrary to Ostrowska et al (2002), we have found no serum NEFA change in pigs fed CLA diets and similar results were found in lactating sows (Bontempo et al, 2004). In this study, betaine had no effect in serum NEFA and similar results have previously been reported (Matthews et al, 1998;Øverland et al, 1999). Furthermore, it is interesting to point out that whole body or hepatic fatty acid oxidation was not affected by betaine in growing pigs (Wray-Cahen et al, 2004), suggesting that reduction in adipose accretion must be via a mechanism other than oxidation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, contrary to Ostrowska et al (2002), we have found no serum NEFA change in pigs fed CLA diets and similar results were found in lactating sows (Bontempo et al, 2004). In this study, betaine had no effect in serum NEFA and similar results have previously been reported (Matthews et al, 1998;Øverland et al, 1999). Furthermore, it is interesting to point out that whole body or hepatic fatty acid oxidation was not affected by betaine in growing pigs (Wray-Cahen et al, 2004), suggesting that reduction in adipose accretion must be via a mechanism other than oxidation.…”
Section: Discussionsupporting
confidence: 88%
“…Although increased total cholesterol (Matthews et al, 2001;Martins et al, 2010) and decreased HDL/total cholesterol (Martins et al, 2010) have been reported in pigs fed betaine, other authors reported no betaine effect on cholesterol, plasma NEFA or TG (Matthews et al, 1998;Øverland et al, 1999). We found decreased HDL/total cholesterol in betaine pigs, but no significant effects in total cholesterol or fractions.…”
Section: Discussioncontrasting
confidence: 56%
“…These findings were unexpected as earlier studies, including those from our laboratory, have not previously demonstrated growth enhancement in animals fed a variety of experimental diets containing similar levels of betaine (Cadogan et al, 1993;Matthews et al, 1998;Overland et al, 1999;Matthews et al, 2001a,b;Fernandez-Fıgares et al,2 002;Lawrence et al, 2002). A new pig growth trial from Finland has recently been published reporting improved feed conversion ratios and daily gains with lower level of dietary betaine (Siljander-Rasi et al, 2003).…”
Section: Discussioncontrasting
confidence: 47%
“…More recent studies in finishing pigs, using various nutritional regimens and experimental conditions have also demonstrated decreases in some indicators of body fat (Lawrence et al, 2002) with a potential reduction in feed intake (Matthews et al, 2001a) under some conditions. In contrast, other studies in finishing pigs have reported minimal or no effects of betaine on growth, feed intake or body fat (Matthews et al, 1998;Overland et al, 1999). In young, feedrestricted pigs, total body composition analysis indicated that betaine was associated primarily with decreased carcass fat, and an increase in protein deposition, particularly at higher levels of betaine intake (Fernandez-Fıgares et al, 2002).Ḿ uch of the evidence from growth trials, including from our lab (Fernandez-Fıgares et al, 2002),ś uggests that betaine may indeed depress overall fat deposition, and this study focused on betaine's potential stimulatory effects on lipid oxidation as a possible mechanism of action for fat reduction in growing pigs.…”
Section: Introductionmentioning
confidence: 66%
“…Supplementation of betaine monohydrate did not improve ileal but faecal dry matter digestibility in piglets (Eklund et al, 2006). Higher ileal or faecal dry matter digestibilities following dietary betaine supplementation have also been reported by (Xu and Yu, 2000) in growing pigs, dietary betaine supplementation had no effect on total tract dry matter digestibility (Øverland et al, 1999(Øverland et al, : FernandezFigares et al, 2008. Also Attia et al (2016) reported that betaine supplementation by 1000 mg / kg to laying hen diet resulted in significant (P<0.001) improve in crude protein, and there are any significant effects on crude fiber, dry matter and ether extract digestibility.…”
Section: Of Betaine On Productive Performance Of Poultrymentioning
confidence: 64%